Design of Multi-channel Ultrasonic Signal Generator Based on FPGA and MCU - TAN Yong; YANG Siqing; LI Hongliang; TAN Qunlin (机车电传动)
With the combination of FPGA and MCU, a multi-channel ultrasonic signal generator design was proposed. Using MCU to implement the USB2.0 data communications and related peripheral control, and using FPGA to carry out the parallel data processing, logic control and waveform output, a combination of both advantages was realized. This paper proposed a set of integrated design and elaborated the internal signal processing of FPGA. The multi-channel ultrasonic signal generator could be used for functional verification and performance testing of the ultrasonic testing equipment.